Risk factors for recurrent neurotrauma: a population-based study in Southeastern Michigan. (19th September 2018) - Hayward, R. David; Fessler, Mary M.; Buck, Joseph; Fessler, Richard D.
ABSTRACT: Introduction : Studies have shown an increased risk of traumatic brain injury (TBI) for individuals who suffer an initial TBI. The current study hypothesized that individuals with recurrent neurotrauma would originate from populations considered 'vulnerable', i.e. low income and/or with psychiatric comorbidities. Methods : Data from the Michigan State Inpatient Database from 2006 to 2014 for the Detroit metropolitan area enlisted a study population of 50 744 patients with neurotrauma. Binary logistic regression was used to assess risk factors associated with admission for subsequent neurotrauma compared with single neurotrauma admission. Results : Patients with repeated neurotrauma admissions were similar to those with one-time trauma in terms of age at first admission and neighbourhood income levels. However, patients with repeated neurotrauma admissions were more likely to be male ( p < .001) and African-American ( p < .001). Comorbid alcohol use and drug use were 39% and 15% less likely to be readmitted with neurotrauma, respectively. Comorbid conditions associated with greater risk of repeat neurotrauma included depression, psychosis, and neurological disorders, increasing risk by 38%, 22%, and 58%, respectively. Conclusion : This study validated the hypothesis that comorbid psychiatric conditions are a significant risk factor for recurrent neurotrauma and validate prior studies showing gender and race as significant risk factors.